2010
DOI: 10.1016/j.envpol.2009.10.033
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tropospheric ozone pollution on trial plot winter wheat yields in Great Britain – An econometric approach

Abstract: Econometric study of British winter wheat trial plot data suggests lower economic loss than predicted from experiments. a r t i c l e i n f o a b s t r a c tNumerous experiments have demonstrated reductions in the yields of cereal crops due to tropospheric O 3 , with losses of up to 25%. However, the only British econometric study on O 3 impacts on winter wheat yields, found that a 10% increase in AOT40 would decrease yields by only 0.23%. An attempt is made here to reconcile these observations by developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Such studies have consistently demonstrated that O 3 can negatively influence a variety of forest responses from crown condition to radial growth [Braun S et al, 2010]. More recently, similar spatially relevant studies have been extended to crop loss assessments [Fishman et al, 2010;Kaliakatsou et al, 2010]. These studies have found that the influence of O 3 can be detected in regional level production statistics and field trial data although damage estimates have been found to differ from those obtained from risk assessments performed using empirically derived dose-response relationships [Kaliakatsou et al, 2010].…”
Section: Impacts On Ecosystems Caused By Omentioning
confidence: 88%
See 1 more Smart Citation
“…Such studies have consistently demonstrated that O 3 can negatively influence a variety of forest responses from crown condition to radial growth [Braun S et al, 2010]. More recently, similar spatially relevant studies have been extended to crop loss assessments [Fishman et al, 2010;Kaliakatsou et al, 2010]. These studies have found that the influence of O 3 can be detected in regional level production statistics and field trial data although damage estimates have been found to differ from those obtained from risk assessments performed using empirically derived dose-response relationships [Kaliakatsou et al, 2010].…”
Section: Impacts On Ecosystems Caused By Omentioning
confidence: 88%
“…More recently, similar spatially relevant studies have been extended to crop loss assessments [Fishman et al, 2010;Kaliakatsou et al, 2010]. These studies have found that the influence of O 3 can be detected in regional level production statistics and field trial data although damage estimates have been found to differ from those obtained from risk assessments performed using empirically derived dose-response relationships [Kaliakatsou et al, 2010]. This may be due to these methods being most effective in those regions characterized by higher average O 3 concentrations [Fishman et al, 2010] where the O 3 signal is strong enough to overcome the influence of confounding variables affecting yield.…”
Section: Impacts On Ecosystems Caused By Omentioning
confidence: 99%
“…Epidemiological studies detected the influence of O 3 in national level agricultural production statistics [14,15]. These studies use statistical multiple linear regression models to analyse 5–30-year time series of historical data to explore the relationship between past crop yield outcomes and trends or inter-annual variations in weather variables (e.g.…”
Section: O3 Effects On Agriculture Forests and Grasslandsmentioning
confidence: 99%
“…A study on soya bean growing across the mid-west USA over a 5-year period was able to detect a 10% reduction in yield [14]. By contrast, only a 0.54% decrease in yield with a 10% increase in O 3 concentrations (characterized using the AOT40 metric (see §3a)) was found at wheat trial sites across the UK over a 13-year period, lower than would be expected according to experimental data [15]. Understanding such discrepancies is important and may be due to the influence of confounding factors (e.g.…”
Section: O3 Effects On Agriculture Forests and Grasslandsmentioning
confidence: 99%
“…, 2017; Saxena et al. , 2020), wheat (Kaliakatsou et al. , 2010; Burney and Ramanathan, 2014), maize (Westenbarger and Frisvold, 1995; Peng et al.…”
Section: Introductionmentioning
confidence: 99%